Peace and Subjectivity - Louis E. Wolcher (Ḥuqūq-i bashar (Online), 2019)
So long as there is law there can be no universal human right to peace. This is because legalized violence, whether in threat or in deed, constitutes the very antithesis of peaceful relations from the point of view of those whom law represses. Law cannot define peace as the absence of all violence—and still less as the absence of all legalized suffering—without gainsaying justice, for as Pascal says, “Justice without might is helpless; might without justice is tyrannical.” Although legal outcomes, like falling boulders and pouncing lions, can always be imputed to historical causes, experience teaches that legal actors generally seek to legitimate their deeds by grounding the law in some non-causal narrative of the right or the good. According to a tenet of political liberalism that can be traced to Descartes’ discovery (or invention) of the irreducible “I” that thinks, the legitimacy of law’s narrative is both given and taken by free and rational politico-legal subjects. In truth, however, the Western philosophical tradition gives us two separate grammars for discussing what it takes to be two different kinds of rational subjects: the causal subject and the grounding subject. The causal subject stands in a relation to the world. Acting strategically as the cause of effects, it uses the object world and other human beings as means to its ends. But the causal subject is also itself caused: its desires and actions are effects of history in the largest sense of the word. Such a one is fated by grammar and custom to become an object and a means in its own right: an object for scientific inquiry and knowledge, for example, and, more generally, a means to the ends of other causal subjects. From the standpoint of the causal subject, there can be no human right not to use or be used as a means. Unlike the causal subject, the grounding subject is supposed to be a genuine origin rather than a mere link in an infinite chain of causes and effects. In Greek terms, this subject is an archē as opposed to an aitia. It also corresponds to the original Latin meaning of the word “sub-ject”: it is thrown (jacere) under (sub) its world as (not in) an unmediated relation to its projects. This second kind of subject has gone by many different names, including “soul” (Plato), “freedom” (Kant) and “Spirit” (Hegel). In one way or another, the idea of the grounding subject performs its primary task within the moral sphere: it is supposed to provide a secure foundation which explains how it is possible for its doppelganger, the causal subject, at once to accomplish something in the world and to refute Plautus’s notorious argument that man is wolf to man. If the causal subject reacts in the manner of an animal, then the grounding subject allegedly responds in the manner of an animal rationale. If the causal subject produces effects, then the grounding subject is supposed to create and bear responsibility for those effects. Given the foregoing distinctions, the most pressing juridical and moral question facing twenty-first century humanity seems to be: How can law and politics become at once effective and just, coercive and compassionate, responsive and responsible? How, in short, is it possible (to borrow Kant’s somewhat quaint terminology) to use oneself and other human beings simultaneously as ends and as means? But here, as elsewhere in philosophy, appearances can be deceiving, for this question presupposes far too much. This paper investigates the strong connection between the foregoing concepts of subjectivity and the notion of a just peace. The question is not, “Are there rational subjects and can they found something new, such as a just peace?” Instead, the question at the heart of the matter is how something as flimsy and ephemeral as an “idea” could ever found anything at all. I will attempt to unmask the terrible tensions or contradictions between justice and ethics, freedom and responsibility, and reason and compassion, and trace them to their origin: the will (or desire) to deny tragedy. I claim that the concept of the grounding subject represents a desperate and ultimately futile attempt to repress awareness of (and evade personal responsibility for) the essential sadness and tragedy of the world. Reason and faith provide the human body with a thin tissue of grounding statements comprised of symbols and images. At best these symbols and images are mere stimuli: action-triggers that will never adequately span the vast existential distance separating the grounding subject from the causal subject, our ends from our means, our words from our deeds, and, more generally, human suffering from the endless secular and religious casuistries we offer to justify it. تا زمانی که قانون وجود دارد هیچ حقوق بشر جهانشمولی برای صلح وجود نخواهد داشت. این به جهت آن است که خشونت قانونی، چه در عمل و چه در تهدید، از دید کسانی که قانون آنها را به اجبار سرکوب می کند، با روابط صلح آمیز بسیار متضاد است. قانون نمیتواند بدون آنکه عدالت را نقض کند صلح را فقدان خشونت تعریف کند. همان طور که پاسکال میگوید: «عدالت بدون قدرت بیفایده و قدرت بدون عدالت مستبدانه خواهد بود.» هرچند عواقب قانونیِ حوادثی مثل سقوط تخته سنگ و چنگ اندازی شیرها همیشه میتواند به دلایل تاریخی نسبت داده شود، اما تجربه به ما میآموزد که بازیگران حقوقی به طور معمول برای قانونی و مشروع نشان دادن اعمالشان، قانون را بر اساس برخی روایتهای غیر علّی از «حق» و «خوب» پایه گذاری میکنند. بر اساس یک انگاره لیبرالیسم سیاسی که نشانههای آن در اختراع یا (کشف) «من» غیر قابل تقلیل، که فکر میکند آشکار میشود، مشروعیت روایت قانون توسط موضوعات آزاد و عقلانی سیاسی-قانونی اعطا و اخذ میشود. به هر حال در حقیقت، نسبت فلسفی غرب به ما دو ساختار جداگانه برای بحث و بررسی آنچه را که مورد نیاز دو نوع موضوعات عقلانی: پایهای و علّی است، ارائه میدهد. موضوع علّی در رابطه با جهان است. عملکرد استراتژیک از آنجایی که منشا اثر است، از جهان مادی و وجود انسان به عنوان غایت خودشان استفاده میکنند. اما موضوع علّی به خودی خود ایجاد میشود: خواستهها و اقدامات آنها متضمن اثرات تاریخی به وسیعترین معنای کلمه است. چنین فردی با چنین ساختار و سنتی تبدیل به یک مقصود و یک وسیله در حق خود میشود: به طور مثال یک موضوع برای تحقیق و دانش علمی و به طور کلی وسیلهای برای اهداف موضوعات علّی دیگر خواهد بود. از دیدگاه موضوع علّی حقوق بشر نمیتواند وجود داشته باشد که مورد استفاده قرار بگیرد یا به عنوان وسیلهای مورد استفاده باشد. برخلاف موضوع علّی تصور میشود که موضوع پایهای یک منبع واقعی باشد، نه صرفا یک پیوند در زنجیره بینهایت علل و اثرات. در اصطلاح یونانی این موضوع یک آرخه در مقابل آیتیا است. همچنین این منطبق با معنای اصلی لاتین کلمه sub-ject است. موضوع دوم توسط بسیاری از مفاهیم مختلف از جمله نفس (افلاطون)، آزادی (کانت) و روح (هگل) تعریف شده است. در هر صورت، ایده موضوع پایهای کار اصلی خود را در حوزه اخلاقی انجام میدهد: این مفهوم قرار است یک پایه امنی ایجاد کند و توضیح دهد که چگونه موضوع علّی به عنوان یک ظهور مظاعف ممکن است و همچنین به رد نظریه پولوتوس مبنی بر اینکه انسان گرگ انسان است، بپردازد. اگر موضوع علّی بر اساس شیوة حیوانی واکنش نشان میدهد، پس موضوع پایهای به شیوه منطقی حیوانات پاسخ میدهد. اگر موضوع علّی عامل ایجاد اثرات باشد، پس موضوع پایهای ایجاد کننده است و مسئولیت آن اثرات را به عهده میگیرد. با توجه به تمایزات ذکر شده به نظر میرسد مهم ترین مسئله حقوقی و اخلاقی بشر که در قرن بیست و یکم قرار دارد این است که: چگونه قانون و سیاست میتوانند به یکباره، موثر و صرف، قهرآمیز و دلسوزانه، پاسخگو و مسئولیت پذیر باشند؟ به طور خلاصه، آیا ممکن است (با استفاده از ادبیات ظریفِ) کانت، از خود و دیگر انسانها، به طور هم زمان به عنوان غایت و وسیله استفاده کرد؟ اما در اینجا مانند جاهای دیگر در فلسفه، ظاهر میتواند فریبنده باشد. زیرا این سئوال پیش فرضهای زیادی دارد. این مقاله ارتباط قوی بین مفاهیم قبلی موضوعیت و صلح را بررسی میکند. سؤال این نیست که «آیا موضوعات منطقی وجود دارد و آیا میتوانند چیز جدیدی مانند صلح عادلانه پیدا کنند؟» در عوض، سؤال اصلی و حیاتی این مسئله این است که چطور چیزی سست و بیدوام، مانند «ایده» قادر است چیزی را پیدا کند؟ من تلاش خواهم کرد تا تنشهای وحشتناک یا تناقضات بین عدالت و اخلاق، آزادی و مسئولیت، عقل و دلسوزی را پیدا کنم و منشا آن را ردیابی کنم: اراده (یا تمایل) به انکار تراژدی. من ادعا میکنم که مفهوم موضوع پایهای بیانگر یک تلاش ناامیدانه و بدون هدف نسبت به خنثی کردن آگاهی (و فرار از مسئولیت شخصی) از غم و اندوه ذاتی و تراژدی جهان است. عقل و ایمان وجود انسان را با یک بافت نازک از اظهارات پایهای که شامل نهادها و تصاویر است میپوشاند. در بهترین حالت این نمادها و تصاویر تنها محرک هستند: اقداماتی که هرگز به اندازه کافی فاصله وسیع وجودی جداکننده بین موضوع پایهای از موضوع علّی را گسترش نمیدهند. همچنین غایات ما از منظورهایمان، سخنان ما از اعمالها، و به طور کلی از رنجهای انسان از سکولار بیپایان و سفسطه مذهبی که در تلاش برای توجیه آنها هستیم.